Tri-axial rubidium and helium optically pumped magnetometers for on-scalp magnetoencephalography recording of interictal epileptiform discharges: a case study - Feys, Odile; Corvilain, Pierre; Labyt, Etienne; Mahmoudzadeh, Mahdi; Routier, Laura; Sculier, Claudine; Holmes, Niall; Brookes, Matthew; Goldman, Serge; Romain, Rudy; Mitryukovskiy, Sergey; Palacios-Laloy, Agustin; et al. (Frontiers in Neuroscience, 2023)
Cryogenic magnetoencephalography (MEG) enhances the presurgical assessment of refractory focal epilepsy (RFE). Optically pumped magnetometers (OPMs) are cryogen-free sensors that enable on-scalp MEG recordings. Here, we investigate the application of tri-axial OPMs ( 87 Rb (Rb-OPM) and 4 He gas (He-OPM)) for the detection of interictal epileptiform discharges (IEDs).IEDs were recorded simultaneously with 4 tri-axial Rb-and 4 tri-axial He-OPMs in a child with RFE. IEDs were identified visually, isolated from magnetic background noise using independent component analysis (ICA) and were studied following their optimal magnetic field orientation thanks to virtual sensors.Most IEDs (>1,000) were detectable by both He-and Rb-OPM recordings. IEDs were isolated by ICA and the resulting magnetic field oriented mostly tangential to the scalp in Rb-OPMs and radial in He-OPMs. Likely due to differences in sensor locations, the IED amplitude was higher with Rb-OPMs. This case study shows comparable ability of Rb-OPMs and He-OPMs to detect IEDs and the substantial benefits of triaxial OPMs to detect IEDs from different sensor locations. Tri-axial OPMs allow to maximize spatial brain sampling for IEDs detection with a limited number of sensors.